2015
DOI: 10.4271/2015-01-1027
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Exhaust Heating to Improve SCR Cold Start Performance

Abstract: SCR cold-start effects are increasingly important for meeting today's emission requirements [1]. A significant challenge toward quickly achieving NOx abatement is the presence of moisture in the catalyst at lower temperatures [1]. This paper describes the ability of an electric heater to effectively raise the temperature of the exhaust and overcome the effect of moisture and low exhaust temperature, allowing NOx conversion to begin sooner. A model of the moisture storage and removal is presented, along with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 6 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…Mera et al [25] implemented a system composed of an electric heating SCR and demonstrated that SCR inlet gas heating at 200 • C had the best deNOx/CO₂ penalty trade-off. The minimum threshold of 200 • C resulted in the best NOx/CO₂ trade-off, reducing on average 4.7 mg of NOx per gram of CO. Culbertson et al [26] studied the capability of an electric heater to effectively raise the temperature of the exhaust and avoid the effect of moisture in low exhaust temperature. This allowed NOx conversion to start earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Mera et al [25] implemented a system composed of an electric heating SCR and demonstrated that SCR inlet gas heating at 200 • C had the best deNOx/CO₂ penalty trade-off. The minimum threshold of 200 • C resulted in the best NOx/CO₂ trade-off, reducing on average 4.7 mg of NOx per gram of CO. Culbertson et al [26] studied the capability of an electric heater to effectively raise the temperature of the exhaust and avoid the effect of moisture in low exhaust temperature. This allowed NOx conversion to start earlier.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on heavy‐duty engines has shown that ~200 s is the usual time taken by the SCR catalyst to reach LOT 28 . Various studies 29,30 have been carried out to improve the catalyst's LOT through thermal management and developing new catalysts. Another factor that drastically reduces the exhaust temperature is the position of the SCR unit in the exhaust system.…”
Section: Introductionmentioning
confidence: 99%
“…27 A study conducted on heavy-duty engines has shown that ~200 s is the usual time taken by the SCR catalyst to reach LOT. 28 Various studies 29,30 have been carried out to improve the catalyst's LOT through thermal management and developing new catalysts.…”
mentioning
confidence: 99%
“…Trends in vehicles hybridisation and electrification make the application of EHC a promising alternative method to other engine-based catalyst heating strategies for future vehicles [21]. The main advantages of an EHC compared to engine-based heating strategies are: i) direct application of thermal energy at the catalyst site [22], ii) the higher degree of control over the heating intensity and period [23], iii) reduced loading of precious metals for catalysts [24] and iv) potential in reducing vehicles' carbon dioxide (CO2) emissions, as the engine can be recalibrated to more efficient conditions [21]. Knorr et al [25] found the potential HC, CO, NOx and CO2 exhaust emission reduction and lower fuel consumption for HEV equipped with EHC coupled with advanced aftertreatment system compared with conventional engine-based catalytic convertor heating strategies.…”
Section: Introductionmentioning
confidence: 99%